3D Cationic Polymeric Network Nanotrap for Efficient Collection of Perrhenate Anion from Wastewater. Issue 20 (21st March 2021) - Li, Xiaorui; Li, Yiming; Wang, Huifang; Niu, Zheng; He, Yingjie; Jin, Linfeng; Wu, Mingyang; Wang, Haiying; Chai, Liyuan; Al‐Enizi, Abdullah M.; Nafady, Ayman; Shaikh, Shoyebmohamad F.; et al.
Abstract: Rhenium is one of the most valuable elements found in nature, and its capture and recycle are highly desirable for resource recovery. However, the effective and efficient collection of this material from industrial waste remains quite challenging. Herein, a tetraphenylmethane‐based cationic polymeric network (CPN‐tpm) nanotrap is designed, synthesized, and evaluated for ReO4 − recovery. 3D building units are used to construct imidazolium salt‐based polymers with positive charges, which yields a record maximum uptake capacity of 1133 mg g −1 for ReO4 − collection as well as fast kinetics ReO4 − uptake. The sorption equilibrium is reached within 20 min and a k d value of 8.5 × 10 5 mL g −1 is obtained. The sorption capacity of CPN‐tpm remains stable over a wide range of pH values and the removal efficiency exceeds 60% for pH levels below 2. Moreover, CPN‐tpm exhibits good recyclability for at least five cycles of the sorption–desorption process. This work provides a new route for constructing a kind of new high‐performance polymeric material for rhenium recovery and rhenium‐contained industrial wastewater treatment. Abstract : A type of cationic polymeric network nanotrap integrated by tetraphenylmethane backbone and imidazolium salt is obtained. This nanotrap exhibits excellent perrhenate collection performance, such as high capacity, fast kinetic, and good selectivity. This work therefore contributes a new general strategy for constructing polymers from 3D‐building units for outstanding performance.